Value creation and value capture in governing shareholder relationships: Evidence from a policy experiment in an emerging market. (30th July 2018) - Jia, Nan; Shi, Jing; Wang, Yongxiang
Abstract : Research Summary : Protecting minority shareholders is a central issue in corporate governance. A common tool of empowering minority shareholders is to curb controlling shareholders' power of expropriating firm value, but this approach was rarely successful because of the resistance from powerful controlling shareholders. We examine an alternative way of empowering minority shareholders without directly fighting with controlling shareholders. A major corporate governance reform in China gave minority shareholders a decision right over certain actions that affected the creation of firm value. We demonstrate that the greater the extent to which minority shareholders' actions can influence the firm's value ex post, the more value controlling shareholders concede to minority shareholders ex ante. This effect becomes even stronger when controlling shareholders are able to expropriate a larger portion of firm value. Managerial Summary : Minority shareholders often have to contend with excessive extraction of firm value by powerful controlling shareholders, particularly in emerging markets. When this tension is considered as a zero‐sum game in which every gain to controlling shareholders has to come from a loss to minority shareholders, controlling shareholders strongly resist any effort to empower minority shareholders. We propose an alternative approach to empower minority shareholders. A major reform of Chinese listed firms bestowed on minority shareholders decision rights to take certain actions that could ex post create a larger "pie" (firm value) for all shareholders. We find that controlling shareholders give away greater value ex ante to minority shareholders to induce more of these actions. Consequentially, minority shareholders are more effectively empowered when they can affect firm value.